From overtourism to undertourism... and back? The struggle to manage tourism regrowth in post-pandemic Amsterdam - Lola Kuenen; Robert Fletcher; Tom Jakobs; Martijn Duineveld; Ko Koens (Boletín de la Asociación de Geógrafos Españoles, 2023)
Amsterdam is one of many cities that has struggled with problems of overtourism in recent years. These problems include nuisance, crowdedness, rising housing prices and economic dependence on tourism. City administrators were aware of these issues and took a variety of measures before the onset of the COVID-19 pandemic, such as placing restrictions on tourism rental (Airbnb) and setting up campaigns to tackle problem behaviour of tourists. Yet when COVID-19 halted the stream of tourists visiting Amsterdam, this created a unique opportunity to make more drastic changes, which the administration has addressed by proposing a new series of measures to proactively help contain tourism regrowth in the post-pandemic period. In this article we critically analyze these strategies to ascertain the extent to which they appear able to address the various issues of pre-pandemic overtourism to which they are aimed. Our analysis demonstrate that while trajectories already started before the pandemic are now being augmented and given more priority and some new strategies to further curb tourism growth are also being implemented, overall Amsterdam remains dominated by a growth-oriented approach to tourism planning.